Unexpected Intraspecific Variability of Perennial Ryegrass (Lolium perenne L.) in Response to Constant Temperature During Germination and Initial Heterotrophic Growth - Ahmed, Lina Q.; Escobar-Gutiérrez, Abraham J. (Frontiers in Plant Science, 2022)
Perennial ryegrass (Lolium perenne L.) is one of the most important forage grasses in temperate grasslands. Climate change in Europe is expected to affect the annual-course of precipitation and monthly average temperatures. Temperature is one of the major factors controlling plant development such as seed germination and plant growth. Breeding perennial ryegrass cultivars adapted to new ranges of temperature could be necessary under most climate change scenarios. However, prior to any breeding effort in such direction, knowing the intraspecific variability of responses to temperature is essential. The objective of this work was to analyse a sample of accessions of L. perenne for their response to constant temperature during germination and initial heterotrophic growth. To this end, eight accessions were taken-out from a genebank containing 160 accessions. Six accessions were wild populations collected in different places in France and the other two were population from a selection program. For germination, four replicates of one-hundred seeds per accession were tested in Petri-dishes in the dark at eight constant temperatures, from 5 to 40˚C with increases of 5˚C. Germination countings were carried out at variable time intervals and durations that depended on temperature treatments. For initial heterotrophic growth analysis, seeds were germinated at 25˚C. Sets of ten seedlings were placed in polypropylene boxes (55 x 120 x 180 mm) on blotter blue paper. Three box-replicates were transferred to each one of the eight constant-temperature treatments in the dark and pictured at variable time intervals. Shoot and root were estimated by image analysis. Neither seed germination nor heterotrophic growth was observed at 40˚C, for any accession. Linear and non-linear regression methods were used for data analysis. Accessions showed significant difference. These results reveal, for the first time, high genetic variability within L. perenne germplasm for the response to temperature in the initial life phases. This discovered variability should serve breeders to create perennial ryegrass varieties for the future.